Green Accounting, Pengungkapan Corporate Social Responsibility dan Profitabilitas Perusahaan Manufaktur - Dewi, Putu Purnama; Wardani, Wardani (E-Jurnal Akuntansi; Vol 32 No 5 (2022), 2022)
This study was conducted to determine the effect of implementing Green Accounting and Corporate Social Responsibility (CSR) Disclosure on the Profitability of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2018-2020. The research population is manufacturing companies that consistently list on the Indonesia Stock Exchange in 2018-2020, namely 158 companies. The sampling technique used in this research is purposive sampling technique using several relevant criteria so that 15 companies or 45 observations are obtained as research samples. The analysis technique used is multiple linear regression analysis technique using SPSS for Windows version 26. Variables of implementing green accounting and disclosure of corporate social responsibility are partially stated to have a positive and significant effect on company profitability. Keywords:  Application of Green Accounting; Disclosure of Corporate Social Responsibility; Profitability.